Drop dead gorgeous : a novel - Gibson, Rachel (Gallery Books, 2022)
"On her way from singing in church to hooking up with a Tinder date, Brittany Lynn Snider crashes her momma's minivan, and her life is changed forever. One moment she's texting HotGuyNate, and the next she's at a hospital in El Paso, watching doctors operate on her near-lifeless body. When a shimmering portal appears, it pull Brittany upward toward heaven--until another patient, a mean girl named Edie, leaps through and steals Brittany's place. Brittany now has a second chance at life on earth, but with a catch: she must inhabit Edie's body in a wealthy suburb of Michigan. As Brittany struggles to adjust to her new life of privilege she rekindles and old flame of Edie's while plotting her escape to Marfa, Texas."--Page 4 of cover.